Down thunder road : the making of Bruce Springsteen - Eliot, Marc; Appel, Mike; Bardon, Ruth; Pantsios, Anastasia; Scott, Jane, 1919-2011; John C. Browning Collection (Rock and Roll Hall of Fame and Museum. Library and Archives); Jane Scott Papers (Rock and Roll Hall of Fame and Museum. Library and Archives) (New York : Simon & Schuster, 1992)
Springsteen's former manager Mike Appel offers author Marc Eliot this behind-the-scenes story of the musician's rise to fame, providing court documents and depositions, along with interviews and more
Includes bibliographical references (p. [357]-370) and index
Keywords: Springsteen, Bruce; Appel, Mike; E Street Band; Rock musicians -- United States -- Biography; Rock music -- United States -- History and criticism; Sound recording executives and producers -- United States -- Biography; Music trade